2000
DOI: 10.1021/jp001721n
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Structure of Vanadium Species in VAPO-5 Molecular Sieves via Density Functional Theory Computation and Raman Spectroscopy

Abstract: Based on the density functional theory calculation using B3LYP hybrid method, a distorted square pyramidal (V 4+ dO)(O f ) 4 unit in a reduced and dehydrated VAPO-5 is formed by the vanadium (IV) oxide ion anchored to two neighboring 12-membered TO 4 rings of the aluminophosphate-5 lattice. By breaking two V-O-T bonds on one twelve-membered-ring to form another VdO bond, V 4+ can be oxidized to a tetrahedral di-oxo V 5+ O 4 unit. The computed structures of vanadium oxide species have been confirmed by Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Such an approach has been successfully used by Pierloot and co-workers for the calculation of d−d transitions and g -values of Co(II) and Cu(II) ions occupying cationic positions in aluminosilicate zeolites, and recently also by Carl et al in DFT calculations of g -values and hyperfine coupling constants of VO 2+ exchanged zeolites. Cheng et al , have applied DFT in combination with X-ray absorption spectroscopy (XANES and EXAFS) to study the structure of vanadyl(IV) and vanadium(V) in cluster models of AlPO 4 -5. The calculated clusters indicated that while the substitution of either P or Al in the framework is not feasible, the parameters of optimized models representing an extraframework substitution site are comparable with those obtained from the in-situ X-ray absorption experiments …”
Section: Introductionmentioning
confidence: 99%
“…Such an approach has been successfully used by Pierloot and co-workers for the calculation of d−d transitions and g -values of Co(II) and Cu(II) ions occupying cationic positions in aluminosilicate zeolites, and recently also by Carl et al in DFT calculations of g -values and hyperfine coupling constants of VO 2+ exchanged zeolites. Cheng et al , have applied DFT in combination with X-ray absorption spectroscopy (XANES and EXAFS) to study the structure of vanadyl(IV) and vanadium(V) in cluster models of AlPO 4 -5. The calculated clusters indicated that while the substitution of either P or Al in the framework is not feasible, the parameters of optimized models representing an extraframework substitution site are comparable with those obtained from the in-situ X-ray absorption experiments …”
Section: Introductionmentioning
confidence: 99%